PERBEDAAN PENGARUH MUSIK BEETHOVEN DAN CHOPIN SELAMA KEBUNTINGAN TERHADAP INDEKS APOPTOSIS NEURON - Dessy Hidayati Fajrin (STIKes MERCUBAKTIJAYA, 2020)
The efforts that can be done to improve brain cells in the prenatal period is the provision of nutrients and good stimulation. Exposure to classical music such as Beethoven can increase the wave of brain activity. During pregnancy, Beethoven music is proven to decrease the apoptosis of neuronal. Laboratory experimental research, posttest-only control group design. Subjects were female pregnant Rattus norvegicus, grouped into 3 random groups: 1 control group and 3 treatments groups; with 6 samples each. Subjects were super ovulated, and 65 dB intensity of music was played for an hour at 8-9 pm on the subjects on 10th day of pregnancy. On 20th day of pregnancy, the mothers were dissected using sectio caesarea. 2 heaviest offspring’ of Rattus norvegicus taken, and their brain tissues are taken as samples. The mean of apoptosis neuronal of rat offspring’ cerebrum were respectively from the low to high levels as follow Beethoven 1,57±0,3 and Chopin 1,77±0,81, control 1,97±0,34. The data were analysed using Kruskal-Wallis test which showed significant differences between four groups p=0,014 in cerebrum. In conclusion, exposure of Beethoven composition during pregnancy gave lower apoptosis of neuronal cerebrum in the offspring-rat compared with Chopin composition.